Օտար յատուկ անունների տառադարձութեան սկզբունքները - Միքայէլեան, Արմէն (տպ. Atlas)
This article is one of the series that deals with the transliteration (transcription) of foreign proper names into Armenian (the way to transcribe foreign names in Armenian characters). The references of the previous articles are: 1) The Principles of Transliterating Foreign Proper Names into Armenian, Part I – Middle Eastern Languages [in Armenian], Haigazian Armenological Review, vol. 40, Haigazian University Press, Beirut 2020, pp. 341-64. 2) The Principles of Transliterating Foreign Proper Names into Armenian, Part II – Classical Languages (Ancient Greek and Latin) [in Armenian], Bazmavep, Year CLXXVIII, Venice 2020, No. 1-2, pp. 304-36. 3) The Principles of Transliterating Foreign Proper Names into Armenian, Part III – French Language [in Armenian], Haigazian Armenological Review, vol. 41, Haigazian University Press, Beirut 2021, pp. 443-466. 4) The Principles of Transliterating (Transcribing) Foreign Proper Names into Armenian, Part IV – English Language [in Armenian], Handes Amsorya, Year CXXXV, Vienna 2021, pp. 197-246. 5) The Principles of Transliterating (Transcribing) Foreign Proper Names into Armenian, Part V – German Language [in Armenian], Bazmavep, Year CLXXX, Venice 2022, No. 1-2, pp. 277-303. 6) The Principles of Transliterating (Transcribing) Foreign Proper Names into Armenian, Part VI – Italian and Spanish Languages [in Armenian], Bazmavep, Year CLXXX, Venice 2022, No. 3-4, pp. 271-300. 7) The Principles of Transliterating (Transcribing) Foreign Proper Names into Armenian, Part VII – Russian (Compared to Other Slav[on]ic Languages) [in Armenian], Haigazian Armenological Review, vol. 42/2, Haigazian University Press, Beirut 2022, pp. 169-198. 8) The Principles of Transliterating (Transcribing) Foreign Proper Names into Armenian, Part VIII – Chinese Language [in Armenian], Bazmavep, Year CLXXXI, Venice, 1-2:2023, pp. 272-305. The present part of the series is devoted to the transliteration (transcription) of names of Japanese origin. The principle of transliteration is based (as in the whole series) on classical Armenian spelling, definitely ruling out “Soviet” transliteration on one side and “Cilician” transliteration on the other. After a reminder of the phonological and orthographic principles of Armenian transliteration mentioned in the first articles of the series, the author scrutinizes the most problematic sounds and phonemes of Japanese and confirms or proposes (based on numerous examples) a coherent and principled transliteration for each of them. The series of articles will continue with two other important languages for the Armenian world – Hindi and Georgian.
Keywords: Լեզուաբանութիւն